1996
DOI: 10.1111/j.1432-1033.1996.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Arabidopsis thaliana Glutathione Synthetase (GSH2) by Functional Complementation of a Yeast Gsh2 Mutant

Abstract: Glutathione (L-y-glutamyl-L-cysteinylglycine, GSH) plays an important role in the protection of plants against various types of stress caused by reactive oxygen species, gazeous pollutants, heavy metals and xenobiotics. A cDNA fragment containing the entire coding unit for glutathione synthetase (GSH2) of Ambidopsis thaliunu was cloned by complementation of the methylglyoxal sensitivity of a gsh2 mutant of the yeast Succharomyces cerevisiae. The cDNA encodes a protein of 478 amino acids (deduced M,: 53 783), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 61 publications
(71 reference statements)
1
32
0
Order By: Relevance
“…In the present report, we observed that manipulating the intracellular glutathione content modulated mitophagy: (i) nitrogen starvation was associated to an early decrease of GSH content; (ii) the addition of NAC maintained (and actually increased) the intracellular level of GSH and prevented mitophagy; (iii) the depletion of GSH by ethacrynic acid (48) reversed the protective effect of NAC on mitophagy; (iv) GSH2 inactivation (49,50) increased the rate of mitophagy; and (v) the addition of a cell-permeable form of glutathione had a similar effect as NAC.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the present report, we observed that manipulating the intracellular glutathione content modulated mitophagy: (i) nitrogen starvation was associated to an early decrease of GSH content; (ii) the addition of NAC maintained (and actually increased) the intracellular level of GSH and prevented mitophagy; (iii) the depletion of GSH by ethacrynic acid (48) reversed the protective effect of NAC on mitophagy; (iv) GSH2 inactivation (49,50) increased the rate of mitophagy; and (v) the addition of a cell-permeable form of glutathione had a similar effect as NAC.…”
Section: Discussionsupporting
confidence: 51%
“…Because mitophagy could be detected only in cells grown on a non-fermentable carbon source, the gsh1 mutant could not be used and we limited the study to the gsh2 mutant. The inactivation of the GSH2 gene led to the absence of detectable glutathione (47,48) and the accumulation of ␥-glutamylcysteine (␥-Glu-Cys) (49). The ⌬gsh2 strain displayed a significantly higher rate of nitrogen starvation-induced vacuolar delivery of mtGFP than the wild type (Fig.…”
Section: N-acetyl-l-cysteine (Nac) Inhibits Nitrogen Starvation-inducedmentioning
confidence: 99%
“…The final step in GSH synthesis is the ligation of glycine with L-y-Glu-Cys catalyzed by GSH synthetase (Gsh2). Genes encoding Gsh2 have been identified in several bacterial and eukaryotic species (Gushima et al, 1984;Mutoh et al, 1991;Peters et al, 1992;Habenicht et al, 1993;Rawlins et al, 1995;Ullmann et al, 1996). However, prior to this study the Saccharomyces cerevisiae gene encoding Gsh2 had not been identified.…”
Section: Introductionmentioning
confidence: 91%
“…The yeast sequence contains the highly conserved glycine-rich domains (Figure 1) that have been suggested to play an essential role in the catalytic activity of GSH synthetases (Ullmann et al, 1996). However, the cysteine residue (Cys-302 in the Arabidopsis sequence), which is conserved in all other eukaryotic enzymes and may play a role in substrate binding (Oppenheimer et al, 1979;Ullmann et al, 1996), is absent from the yeast sequence. Similar to the other eukaryotic Gsh2 enzymes, hydropathy analysis of the yeast Gsh2 indicated a pattern typical of a soluble protein.…”
Section: Determination Of Gsh Levels and Gshl And Gsh2 Enzyme Activitiesmentioning
confidence: 99%
See 1 more Smart Citation